(untitled) (Clinical Sociology Review, 2025)
This article provides a comprehensive overview of the concept of subjectivation, as it can be understood in clinical sociology. The aim is to justify the focus on this concept, preferred to that of the subject, and to emphasize its processual dimension. Subjectivation is defined as a process caught in multiple dialectical movements, linking therapeutic and political subjectivations, desubjectivation and resubjectivation, subjugation and emancipation, recognition of one’s desire and desire for recognition, determinism and freedom, meaning and action, and self-affirmation and destruction. This complicates the definition of subjectivation: it involves grasping the subjective shifts through which individuals seek to grasp and grasp the socio-psychological processes in which they are engaged, so that they can reclaim their agency and the meaning of their lived experiences by performing meaningful actions and by giving meaning to their actions. However, these dialectical movements break with a romantic conception of subjectivation, integrating into its understanding its precarious, fleeting, partial, indefinite, and ultimately interminable characteristics. Moreover, in order to grasp the socio-anthropological and psychological conditions of possibility for subjectivation processes, it seems heuristic to link this concept to those of historicity and negativity. Finally, a dialogue with the critical analysis of capitalist subjectivation proposed by Pierre Dardot and Christian Laval allows us to question the political and emancipatory scope of collaborative research mechanisms in clinical sociology.